Interpretation of the Tribeč Mts. deep geological structure based on results of geophysical, mainly magnetotelluric modelling - BEZÁK, Vladimír; VOZÁR, Ján; HVOŽDARA, Milan (Contributions to Geophysics and Geodesy, 2011)
Magnetotelluric measurements (MT) in the southeast (SE) part of MT–15profile in the frame of CELEBRATION 2000 project identified a subhorizontal zone withhigher conductivity in the depth of cca 2–6 km below the Tribeč Mts. surface. This zone isinterpreted as a complex of metamorphic rocks under the tectonically overlaying granites.The original presuppositions collected through other geophysical methods on the existenceof such a complex are thereby confirmed. Apart from this finding, the MT measurementsidentified other conductive zones in the Tribeč mountain range and its surroundings.Those are close to the surface and belong to sedimentary rocks and volcanites. Thesteep, narrow and deeply penetrating conductive zone at the north-western edge of TribečMts. can be interpreted as a deep Neogene shear zone. Subhorizontal conductive zonein SE part of the cross-section under the volcanic complexes is interpreted as the oldermylonitized zone. This zone may be saturated by fluids, and is possibly of carbon originand mineralized, connected with volcanic activity.